Жисмоний маданият факультетлари талабаларининг асосий гимнастика воситалари орқали касбий фаолиятини ошириш муаммолари - Тойлибаев, С.М (FAN va JAMIYAT, 2022)
The article talks about the increase and development of the professional activity of students of the faculties of physical culture with the help of basic gymnastics.